Marx, Engels e Tocqueville: a pobreza no pensamento social do século XIX - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Poverty is a theme strongly present in social sciences, even though the definition of the term itself is a matter of debate. In search of a deeper understanding of the origins of social thought regarding this phenomenon, we researched 19th-century literature for the first works that brought poverty as a primary object. By way of introduction, we surveyed the “poor laws” in England, the first attempts to classify and control the problem we know today as poverty. Next, we proceeded to examine the works of Marx, Engels, and Tocqueville in search of their reflections and propositions about poverty in the European societies of their time. We observed that, while Tocqueville's writings have a more descriptive character and his reflections on the subject faithfully reflect the dominant thought of his time, Marx and Engels seek a deeper theorization and move towards a new school of thought that is not just about poverty, but about the fate of the entire working class. Such differences are mainly explained by the epistemological and methodological choices of the authors, with Tocqueville aligned with a liberal democratic tradition and Marx and Engels with the nascent socialism that both classified as “scientific”.
Marx, Engels, and Tocqueville: the poverty in 19th century's social thought
Marx, Engels y Tocqueville: la pobreza en el pensamiento social del siglo XIX
Keywords: .; .; .; CIENCIAS HUMANAS: SOCIOLOGIA: FUNDAMENTOS DA SOCIOLOGIA: TEORIA SOCIOLOGICA; Pobreza; Sociologia clássica; Pensamento social; Marxismo; Poverty; Classical sociology; Social thought; Marxism